2020
DOI: 10.7759/cureus.9221
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Methods of Height Estimation and Their Impact on Low Tidal Volume Ventilation in a Mixed Ethnicity Intensive Care Unit: A Real-World Experience

Abstract: Background Height measurement is crucial for calculating predicted body weight (PBW) and establishing low tidal volume ventilation (LTVV). However, standing height is usually unavailable in critically ill patients and supine height may be difficult to obtain. Objective We investigated whether there were any significant differences in tidal volumes (VT) obtained using PBW derived from supine, forearm, and lower leg lengths in an intensive care unit (ICU) setting. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Singh et al concluded that forearm length overestimates predicted body weight and tidal volume in Indians and Africans. They used supine height as a comparison [35].…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al concluded that forearm length overestimates predicted body weight and tidal volume in Indians and Africans. They used supine height as a comparison [35].…”
Section: Discussionmentioning
confidence: 99%